2004
DOI: 10.2320/matertrans.45.2295
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of Plastically-Accommodated Steady-State Creep of a Composite

Abstract: Composite creep deformation was analyzed, based on a continuum plasticity representation of the matrix, in an ideal composite at high temperatures in the case of negligible interfacial diffusion and sliding. A general formula of the steady-state creep strain rate was derived for a composite consisting of an ellipsoidal rigid reinforcement and a creeping matrix with a stress exponent of one. A closed-form solution was then derived for a composite with a cylindrical reinforcement under pure shear deformation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, they showed that load was no longer transmitted to the rigid reinforcing phase at zero interfacial strength, and that the creep strength under such a situation was lower than that of the matrix alone. Sato et al 13,14) studied the creep behaviors of MMCs with rigid reinforcing phases and showed that composite weakening and dispersion strengthening occurred in the low-stress region, where the strain gradient was +1 This Paper was Originally Published in Japanese in J. Japan Inst. Met.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed that load was no longer transmitted to the rigid reinforcing phase at zero interfacial strength, and that the creep strength under such a situation was lower than that of the matrix alone. Sato et al 13,14) studied the creep behaviors of MMCs with rigid reinforcing phases and showed that composite weakening and dispersion strengthening occurred in the low-stress region, where the strain gradient was +1 This Paper was Originally Published in Japanese in J. Japan Inst. Met.…”
Section: Introductionmentioning
confidence: 99%